FUTURE TEACHERS’ TRAINING FOR IMPLEMENTATION OF INDIVUDUAL APPROACH TO STUDENTS ON THE LESSONS OF LABOUR TRAINING AND TECHNOLOGIES - Turanov, Yurii; Uruskyi, Andrii (Educological discourse, 2019)
Relevancy of training future teachers of labor training and technologies for implementation of individual approach to students’ learning has been substantiated. Complex of actions to be taken into account for the successful execution of individual approach to the students’ learning has been determined: identification of the basic individual peculiarities of students, which are manifested while studying particular subject; considering age features, defining students’ individual characteristics in order to take them into account in the process of learning, grouping students, developing differentiated tasks for students of different groups. Training of future teachers of labor training and technologies for individual approach implementation in accordance with stages and with gradual complication of tasks has been suggested. Notional stages of students’ training for the implementation of individual approach have been determined: initial understanding of the role of individual approach to students; learning of the essence of individualization and differentiation of training, creation of differentiated tasks; development of creative tasks taking into account individual and age features; formation of professional competencies in future teachers and consolidation of the existing knowledge and skills in implementing individual approach to students; improving the readiness of students to implementation of individual approach. A list of theoretical questions for students in order to understand the essence and peculiarities of implementation of individual approach to teaching students has been suggested. Requirements to the tasks on training future teachers for implementation of individual approach in teaching students in accordance with each stage have been developed.